Pengaruh Work-Life Balance dan Dukungan Rekan Kerja Terhadap Kinerja Pegawai Perusahaan Daerah Air Minum (PDAM) Tirta Limutu - Yusuf, Zulkifli; Yakup; Ishak, Olfin (Pusat Riset dan Inovasi Nasional, 2025)
This study was conducted to determine: 1) the influence of work-life balance on employee performance at PDAM Tirta Limutu, Gorontalo Regency, 2) the influence of co-worker support on employee performance at PDAM Tirta Limutu, Gorontalo Regency, and 3) the influence of work-life balance and co-worker support on employee performance at PDAM Tirta Limutu, Gorontalo Regency. This study is associative with a quantitative approach, which aims to analyze the relationship between the variables studied. The data analysis method used is multiple linear regressions. The primary data analyzed was obtained through interviews and direct observation of the research object. The data collection process was carried out by distributing questionnaires to respondents. At the same time, the sampling technique used the census method, where the entire population was used as a sample in this study. The results of the study indicate that partial work-life balance (X1) has a positive and significant effect on the performance of PDAM Tirta Limutu employees in Gorontalo Regency, support from co-workers (X2) has a positive and significant effect on the performance of PDAM Tirta Limutu employees in Gorontalo Regency. Simultaneously, work-life balance and support from co-workers positively and significantly affect the performance of PDAM Tirta Limutu employees in Gorontalo Regency.